From blight to bright: crafting sustainable feasibility for brownfield site / Najma Azman ... [et al.] - Azman, Najma; Abdul Majid, Nurauni Nadiah; Zulkupli, Muhammad Afiq; Mohd Nizam, Nur Arifah Zahra (2024)
Urban regeneration strategies often involve redeveloping brownfields, which differ significantly from greenfields due to the presence of existing structures. The abandonment of these properties has resulted in wasted land resources and adverse effects on the economy, society, and the environment. This study aims to assess the redevelopment potential of a specific brownfield site and propose an appropriate building layout. A comprehensive desktop analysis was conducted, which included demographic and population studies to gather relevant information for the redevelopment proposal. Additionally, a SWOT analysis was employed to evaluate the strengths, weaknesses, opportunities, and threats associated with the site. The research identified the Pandan Safari Lagoon Waterpark as an optimal site for redevelopment into sports and recreational facilities. The findings suggest that redeveloping this brownfield site can significantly enhance economic viability, improve societal well-being, and promote environmental sustainability. The proposed layout demonstrates considerable potential for successful implementation and commercial viability. By transforming the brownfield site into a hub for sports and recreation, the redevelopment plan promises to revitalise the area, providing numerous benefits to the local community and environment. This study highlights the importance of strategic planning in the redevelopment of brownfields to maximise their potential and mitigate associated challenges.